Removal of Rhodamine-B From Aqueous Solution by Adsorption Onto Chitosan/Polymethylmetacryalte/Cloisite-10A Composites - Eny Kusrini (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
The aim of this study was to investigate the use chitosan/polymethyl methacrylate/cloisite-10A (Chi/PMMA/Cloi) composites as an adsorbent for Rhodamine-B. The Chi/PMMA/Cloi composites were synthesized by solution induced intercalation method. The properties of the composites were investigated by using Fourier transform infrared spectroscopy (FTIR), and Scanning electron microscopy (SEM). The effects of polymethyl methacrylate (PMMA) loading and contact times on the adsorption process of Rhodamine-B were investigated. The results show that the adsorption capacity for the Rhodamine-B increased with increase in contact times but there was not significant change observed with respect to increase in PMMA loading. Abilities of Chi/PMMA/Cloi composites to adsorb rhodamine-B were higher than those found in the pristine of cloisite-10A, chitosan, and PMMA, respectively. The adsorption capacity of rhodamine-B from solution by using the composites was reached 89.20 – 91.58% with contact times from 40 - 120 min. The results indicate that the Chi/PMMA/Cloi composites can be used for the removal of rhodamine-B from aqueous solutions.